Crisis, miracles, and beyond : negotiated adaptation of the Danish welfare state - Albæk, Erik (Aarhus University Press ; David Brown Book Co. [distributor], 2008)
How did Denmark avoid a macroeconomic catastrophe in the 1980s and 1990s and still manage not only to maintain but also expand its welfare state? Critics of the welfare state identified the vices behind Denmark's macroeconomic troubles as its enormous, thoroughly unionized, and unresponsive public sector combined with the large numbers of people who relied on the welfare state for their livelihood and thus made programmatic cuts politically difficult. Taxes for this welfare state compressed investment, eroding both fiscal and current account balances. Yet by the mid-1990s, public support for t.